Exploratory Factors Analysis of Shaping Phubbing Behavior in Adolescents - Annisa Qurrotu Ainy; Sri Maslihah; Anastasia Wulandari (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2022)
This research aimed to identify factors shaping phubbing behavior among adolescents in West Java. The research used mixed methods, including a qualitative stage to examine item themes with 100 respondents and a quantitative stage to identify psychometric characteristics with 1,016 respondents. The data analysis technique employed in the qualitative stage was open coding, while the quantitative stage involved two techniques, specifically Exploratory Factors Analysis (EFA) and measurement model testing using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The combination of qualitative and quantitative analysis techniques allows for a more comprehensive understanding of the data. The results showed that the instrument construct has high-reliability coefficients (α = .79). The convergent validity value shows outer loadings > .7 and AVE > .5, and discriminant validity with cross-loading and Fornell-Lacker higher than other latent variables. Typical factors shaping phubbing behavior are found among adolescents, including withdrawal, compulsion, and euphoria.